The Leadership Styles of Head Nurses Working in the Training Hospitals Affiliated to Zanjan University of Medical Sciences in 2020 - Jafar Matini; Nasrin Bahrami Nejad; Nasrin Hanifi; Ramezan Fallah (Zanjan University of Medical Sciences and Health Services, 2022)
Background: The physical-mental health status of health care providers and patients can be influenced by the leadership styles of head nurses and health centers managers. Objectives: The current study aimed to study the leadership styles of head nurses working in the training hospitals of Zanjan in 2020. Methods: In the current descriptive study 346 nurses working in the training hospitals wards affiliated to Zanjan University of Medical Sciences participated through cluster random sampling. A tool including demographic and Multifactor Leadership Questionnaire was used to collect data. Data were analyzed using descriptive- inferential tests such as mean, standard deviation and analysis variance and LSD by SPSS software version 25. Results: Head nurses adopted transformational (3.02+0.61), laissez-fair (2.94+0.92) and transactional (2.81+0.53) leadership styles, respectively. The relationship between the leadership styles and the type of hospitals and the wards was significant (p<0.05). Bu Ali Sina Hospital had the highest percentage of using transformational and laissez-fair leadership styles and Ayat -Allah Mousavi Hospital had the highest percentage of using transactional leadership style as well. Concerning the wards, pediatric and neonatal wards used the most of the transformational leadership style and the highest percentage of using transactional and laissez-fair leadership styles was associated with psychiatric ward. Conclusion: Due to the superiority of transactional leadership style over the laissez-fair leadership style, it can be said that head nurses give less freedom to the nurses working in their wards. Therefore, motivating head nurses to be innovative and further use of laissez -fair leadership style is recommended.